PENGARUH PENAMBAHAN SERAT BAMBU PADA PEMBUATAN PAVING BLOCK TERHADAP KUAT TEKAN - Nur, Marwan; Harsusani, Harsusani; Aida, Nur (Universitas Muhammadiyah Palembang, 2024)
Bamboo is widely used for various forms of building construction, such as houses, as roofs, columns and foundations. Apart from that, the remainder of its use will become waste. One of the building materials that is often used is paving blocks as an alternative ground surface cover that can be used for road pavement, parking lots, pedestrians, parks, etc. The aim of this research was to determine the effect of adding bamboo fiber with variation of 1%, 3%, and 5% on the compressive strength of paving blocks. The method used in this research is the experimental method. Primary data consists of material testing results and paving block compressive strength. Research was conducted at the Structures and Materials Laboratory, Departement of Civil and Mining Engineering, Ketapang State Polytechnic. From the results of the compressive strength testing of paving blocks that have been carried out, the highest average value of compressive strength of paving blocks with a variation of 1% is 320.01 kg/cm2 which corresponds to the quality concrete C used for home garage pavement, pedestrian circulation, and parking lot.